The Vague, the Viral, the Parasitic: Piranesi’s Metropolis - Teresa Stoppani (Footprint)
In mid-18th century Giovanni Battista Piranesi’s etchings systematically document the old and new monuments, decrepit buildings and broken down infrastructures of a Rome that continues to inhabit and reinvent its past. His views of Rome offer a devastating account of the blurring of distinctions and articulations that time, use and neglect have imposed on the old differentiations of the urban and the rural, the public and the private, the monumental and the domestic in the 18th century city. Rome becomes for Piranesi the laboratory for a questioning of architecture that places his work well beyond the debate on style and on the origin that dominated the architectural discourse of his time. This paper suggests that Piranesi’s images anticipate the dispersion and sprawl of the city of today, in which the ‘vague’, the ‘viral’ and the ‘parasitic’ become modes of inhabitation and of transient negotiated definition.